Students' Perception of Role-Play as a Technique to Teach Speaking Skill to Eleventh Grade Students in Senior High School - Wafa, Dafi Imaduddin (Universitas Negeri Surabaya, 2022)
Theobjectiveofthestudyistoimproveeleventhgradestudents’speakingskillsusingrole-playasatechnique atMABi’rulUlumSidoarjo.Duringtheconduct,theresearcherinvolvedthesupervisingteacherandthelanguage teacherofgradeEleventhLanguageclass.Thetargetoftheresearch was18studentsofgradeXIofScience classofMadrasahBi’rulUlumSidoarjowithintheacademicyearthenselected6studentsamongtheclassfor the researchusing role-play as a technique. The researcher received the data from the questionnaire, students’interviews, observation, and video recordings were used as instruments to gather data during the implementationoftheaction.Theresearcherconductedtwophases ofactionforthisstudy.The study's results indicated that the implementation of role play as a technique effectively improves students’ speaking skills.The role play technique is shown to be effective in increasing students’ speaking skills because itmotivates the students to learn to speak, confidence in speaking, and boosts their interaction. This indicates thattherole-playtechniqueresultedinpositivefeedbackonstudents’performanceimprovementinlearning.